Job Search and Hiring with Two-Sided Limited Information about Workseekers' Skills - Eliana Carranza; Robert Garlick; Kate Orkin; Neil Rankin (Institute of Labor Economics (IZA), 2021)
We present field experimental evidence that limited information about workseekers' skills distorts both firm and workseeker behavior. Assessing workseekers' skills, giving workseekers their assessment results, and helping them to credibly share the results with firms increases workseekers' employment and earnings. It also aligns their beliefs and search strategies more closely with their skills. Giving assessment results only to workseekers has similar effects on beliefs and search, but smaller effects on employment and earnings. Giving assessment results only to firms increases callbacks. These patterns are consistent with two-sided information frictions, a new finding that can inform the design of information-provision mechanisms.
Keywords: J23; J24; J31; J41; O15; O17; 330; skills; job search; employment; wages; labor markets; active labor market